Analisis Perilaku Siswa Kelas XII Ph (Perhotelan) dan Tata Boga Selama Mengikuti Pelajaran Bahasa Inggris disekolah SMKS Praja Pandawa Bangli - Ni Wayan Pebriyanti; I Putu Oka Suardana (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This research was conducted to analyze student behavior in participating in the English learning process at school. This research uses qualitative descriptive techniques. The object of this research was 40 students in class XII of Hospitality and Culinary Management at Praja Pandawa Bangli Vocational High School. Data was collected through a system of observation, questionnaires and direct student and teacher interviews. This data analysis was obtained from observations in the field regarding students' attitudes or behavior when participating in the learning process. This foreign language is one of the languages that they must learn as prospective tourism actors. English has now become a mandatory language for tourism vocational students. Apart from language skills, what we need to pay attention to is that behavior or attitude is what really underlies everything we do. We don't only teach education about student behavior at school, but the role of parents is the most important. We can teach attitude, but change is based on each individual, as educators we can only give direction and direct, in the process the individual has the main role.